Characterization of coconut oil from cold plasma-treated coconut flakes and protein-dependent whipping behavior in plant-based cream systems - Enxi Fu; Junxia Jiang; Yang Chen; Pengyin Li; Huibei Sun; Zihan Zhang; Ruihao Chi; Dongyu Hu; Changyi Chen; Yuqi Wang; Tian Li; Weimin Zhang (Food Research International, 2026)

A novel intramolecular amino synergism driven AEEA-DEEA-Sulfolane-H2O hybrid phase change absorbent for energy-efficient CO2 capture - Yuqi Zhang; Daofan Ma; Taotao Fu; Chunying Zhu; Youguang Ma (Chemical Engineering Journal, 2026)

Microbial production of D-arabitol from D-xylose by engineered Trichosporonoides oedocephalis: Fermentation performance and salt-stress transcriptional responses - Yue Tang; Xin Ju; Yuqi Peng; Zhicheng Xie; Wei Liu; Jiaolong Fu; Jiajia Chen; Liangzhi Li (Food Bioscience, 2026)

Coordination-driven self-assembly of cerium-baicalein nanozyme promotes spinal cord injury repairing by simultaneously scavenging mitochondrial ROS and reprogramming macrophage polarization - Zhefan Xie; Cheng Peng; Xiaofeng Li; Yuqi Zhao; Shenghang Liu; Xuenian Ye; Yuxue Wang; Wenchong Tan; Huimin Hu; Jianqiang Li; Yanming Ma; Chunlai Fu (Chemical Engineering Journal, 2026)

Screening of typical pollutants in groundwater polluted by nitrogen heterocyclic pesticides and removal mechanism of iron-doped biochar - Renchuan Fu; Kai Liu; Dan Qu; Yuqi Qi; Xiaochen Qi; Chih-Huang Weng; Yanru Hao; Na Liu; Chunyu Wen (Journal of Environmental Sciences, 2026)

Pioneer plant facilitates microbial community assembly by improving physicochemical and mineralogical properties of iron ore tailings - Xinyu Wu; Hui Wu; Wei Fu; Qiong Wang; Yunjia Liu; Yuqi Wu; Suixiaochen Chen; Baodong Chen; Songlin Wu (Journal of Environmental Sciences, 2026)

Engineering catalytic sites in ZnIn2S4 via Mg doping: A S-to-In shift toward enhanced photocatalytic H2 evolution - Yan Wang; Yuqi Shi; Xin Chong; Chao Wang; Rong Fu; Chang Liu; Yuelan Zhang (Chemical Engineering Journal, 2026)

Recent developments in braided river morphology of the Tuotuo River in the upper Yangtze River basin - Tingting Jiang; Xinmeng Zheng; Hongsheng Fu; Qianyue Guo; Xingnian Liu; Yuqi Shan; Vladimir I. Nikora; Chao Liu (Environmental Fluid Mechanics, 2026)

Bidirectional electron transfer enabled by dual electric fields for efficient 4-nitrophenol removal on a bifunctional FeCoNiP/PCN heterojunction - Yan Wang; Chang Liu; Rong Fu; Chao Wang; Xin Chong; Yuqi Shi; Yuelan Zhang (Journal of Environmental Chemical Engineering, 2026)

Optimization investigation on the novel MEA-MDEA-n-butanol-H2O phase change absorbent for CO2 capture - Yuqi Zhang; Yaxuan Zhen; Chunying Zhu; Taotao Fu; Youguang Ma (Chemical Engineering Journal, 2026)

A wheat posture monitoring and analysis system based on keypoint detection - Bing Han; Zhuangzhuang Sun; Shouyang Liu; Yuqi Cao; Jianbo He; Yifan Zhu; Hongwen Zhang; Zhengxin Fang; Xiuqing Fu (Computers and Electronics in Agriculture, 2025)

Mechanisms for maintaining the stability of heterotrophic nitrification and aerobic denitrification in a synthetic microbial community under mixed nitrogen stress: Insights into community dynamics and metabolic features - Yuqi Qi; Minmin Chen; Chih-Huang Weng; Yanru Hao; Renchuan Fu; Xiao Liu; Chao Yan; Haolang Liu; Na Liu; Yaoming Su (Chemical Engineering Journal, 2025)

Differential diagenetic controls on petrophysical heterogeneity of lacustrine beach-bar tight sandstones: Insights from the Boxing Sag, eastern China - Cunfei Ma; Haowen Song; Yuqi Wu; Xiaopeng Cao; Haicheng Liu; Huafeng Zhang; Yong Fu; Wei Wang; Chao Huang; Xianxu Fang (Marine and Petroleum Geology, 2025)

Stage–discharge relationships in vegetated channels with overbank floods - Hongsheng Fu; Yuqi Shan; Marwan A. Hassan; Kejun Yang; Chao Liu (Journal of Hydrology, 2025)

Advanced carbon-based materials for room-temperature potassium-sulfur batteries - Xiaomin Yuan; Xiaoqi Shi; Yuqi Zhao; Jiaxing Fu; Fanglin Yu; Jiancheng Guo; Chuanhua Tang; Jinping Ma; Jinkui Feng (Fuel, 2025)

Deciphering the microbial players driving straw decomposition and accumulation in soil components of particulate and mineral-associated organic matter - Yingyi Fu; Yuqi Xu; Qiang Wang; Lukas Van Zwieten; Chao Liang; Jianming Xu; Georg Guggenberger; Yu Luo (Soil Biology and Biochemistry, 2025)

Transformation of microplastics during UV-LED based water disinfection: Mechanistic insights and environmental implications - Jieli Ou; Yuqi Tang; Ehiaghe Agbovhimen Elimian; Xinyu Yang; Yiqing Liu; Yongsheng Fu; Mohamed Gamal El-Din (Journal of Hazardous Materials, 2025)

A comparative investigation on carbon dioxide capture performance and applicability of three novel choline amino acid ionic liquid aqueous solutions - Yuqi Zhang; Daofan Ma; Taotao Fu; Chunying Zhu; Youguang Ma (Chemical Engineering Journal, 2025)

Branch segmentation and phenotype extraction of apple trees based on improved Laplace algorithm - Long Li; Wei Fu; Bin Zhang; Yuqi Yang; Yun Ge; Congju Shen (Computers and Electronics in Agriculture, 2025)

Simple and robust method for the quantification of nine organic acids in beer using 3-chloropropyl bonded C18 materials with HPLC-UV analysis - Yu Shi; Huifan Li; Yuqi Lu; Ming Chen; Hua Yang; Dongmei Fu (Systems Microbiology and Biomanufacturing, 2025)

The role of social media in tourists’ conformity and irrational food consumption: Implications for food waste - Yuqi Zhang; Fu-Chieh Hsu; Lihua Gao (International Journal of Gastronomy and Food Science, 2025)

Preparation of diacylglycerol by lipase-catalyzed glycerolysis in the presence of polar adsorption materials - Xiao Tang; Houyue Li; Jialing Gu; Yijie Fu; Junwen Yu; Zongrun Li; Yuqi Li; Xiaowen Wang; Xiaosan Wang (Food Chemistry, 2025)

Enrichment of a heterotrophic nitrifying and aerobic denitrifying bacterial consortium: Microbial community succession and nitrogen removal characteristics and mechanisms - Yuqi Qi; Renchuan Fu; Chao Yan; Xiao Liu; Na Liu (Bioresource Technology, 2025)

Tremendously enhanced catalytic performance of Fe(III)/peroxymonosulfate process by trace Cu(II): A high-valent metals domination in organics removal - Jieli Ou; Yiqing Liu; Linyue Zhang; Zhenran Wang; Yuqi Tang; Yongsheng Fu; Dandan Zhao (Journal of Environmental Sciences, 2025)

Comprehensive susceptibility assessment of continental glacier ice avalanches: a case study of glaciers on the northwestern Tibetan Plateau - Yuqi Shang; Hao Sun; Gaojian Miao; Chao Wang; Jinfeng Liu; Wentao Zhang; Huaquan Yang; Hang Fu (Landslides, 2025)

Symbiont-mediated antisense RNA delivery controls Nosema ceranae infections in Apis mellifera - Sihan Wang; Haoyang Li; Ruyi Shi; Yuqi Fu (Journal of Invertebrate Pathology, 2024)

Bacterial outer membrane vesicles-clothed nanoparticles delivered by live macrophages for potentiating antitumor photoimmunotherapy - Cong Fu; Lu Tang; Yuqi Cao; Yue Yin; Hening Liu; Jingwen Feng; Jifan Gao; Jing Li; Wei Wang (Chemical Engineering Journal, 2024)

Micro/nano system-mediated local treatment in conjunction with immune checkpoint inhibitor against advanced-Stage malignant melanoma - Lu Tang; Hening Liu; Yue Yin; Ting Pan; Cong Fu; Yuqi Cao; Yijun Mei; Qiaqia Xiao; Ziwei Yan; Yi Yao; Haijuan Dong; Wei Wang (Chemical Engineering Journal, 2024)

Research on copper flow and environmental load in China's new infrastructure industry for carbon neutrality - Yuqi Lu; Guangxin Liu; Qiang Yue; Yingjie Fu; Heming Wang; Zhihe Dou; Yisong Wang; Tao Du (Journal of Cleaner Production, 2024)

Size-switchable and dual-targeting nanomedicine for cancer chemoimmunotherapy by potentiating deep tumor penetration and antitumor immunity - Lu Tang; Yue Yin; Ziyao Zhang; Cong Fu; Yuqi Cao; Hening Liu; Jingwen Feng; Jifan Gao; Jing Shang; Wei Wang (Chemical Engineering Journal, 2024)

Distinct photochemistry of adsorbed and coprecipitated dicarboxylates with ferrihydrite: Implications for iron reductive dissolution and carbon stabilization - Qingchao Li; Yu Fu; Lingli Wang; Jinhui Cao; Yuqi Xia; Zhen Zhang; Zhaohui Wang (Science of The Total Environment, 2024)

Discharge evolution law of debris flow based on a sharp bend physical modeling test - Ming Lu; Hao Sun; Jinfeng Liu; Abrar Hussain; Yuqi Shang; Hang Fu (Journal of Mountain Science, 2024)

Early detection of rubber tree powdery mildew using UAV-based hyperspectral imagery and deep learning - Tiwei Zeng; Yong Wang; Yuqi Yang; Qifu Liang; Jihua Fang; Yuan Li; Huiming Zhang; Wei Fu; Juan Wang; Xirui Zhang (Computers and Electronics in Agriculture, 2024)

Phosphate-mediated degradation of organic pollutants in water with peroxymonosulfate revisited: Radical or non-radical oxidation? - Lingli Wang; Qingchao Li; Chunxiao Xu; Yu Fu; Yi Tang; Pu Wang; Zhen Zhang; Yuqi Xia; Xiaojing Liu; Jinhui Cao; Sifan Qiu; Yanna Xue; et al. (Water Research, 2024)

Stage–discharge relationship in an erodible compound channel with overbank floods - Hongsheng Fu; Yuqi Shan; Kejun Yang; Yakun Guo; Chao Liu (Journal of Hydrology, 2024)

Synergistic degradation of oxytetracycline and rhodamine B in Cu(II)/peroxymonosulfate process: Two distinct oxidation mechanisms - Jieli Ou; Yiqing Liu; Linyue Zhang; Zhenran Wang; Yuqi Tang; Yongsheng Fu; Dandan Zhao (Journal of Environmental Chemical Engineering, 2024)

Storm-induced nitrogen transport via surface runoff, interflow and groundwater in a pomelo agricultural watershed, southeast China - Yao Wang; Fenfang Wang; Yan Fang; Yuqi Fu; Nengwang Chen (Environmental Pollution, 2024)

Unraveling the mechanisms behind sodium persulphate-induced changes in petroleum-contaminated aquifers’ biogeochemical parameters and microbial communities - Yuqi Qi; Jun Zeng; Junshi Tao; Rentao Liu; Renchuan Fu; Chao Yan; Xiao Liu; Na Liu; Yanru Hao (Chemosphere, 2024)

Prioritizing ecological restoration in hydrologically sensitive areas to improve groundwater quality - Yao Wang; Yiqi Yu; Xin Luo; Qiaoguo Tan; Yuqi Fu; Chenhe Zheng; Deli Wang; Nengwang Chen (Water Research, 2024)

Hydroxy fatty acids in the surface Earth system - Wenxin Zhang; Wei Hu; Quanfei Zhu; Mutong Niu; Na An; Yuqi Feng; Kimitaka Kawamura; Pingqing Fu (Science of The Total Environment, 2024)

Staphylococcus warneri strain XSB102 exacerbates psoriasis and promotes keratinocyte proliferation in imiquimod-induced psoriasis-like dermatitis mice - Wenhao Si; Min Li; Kuan Wang; Jialin Li; Mengke Xu; Xiaoyue Zhou; Jie Bai; Zhiyuan Qu; Guoyan Song; Xueya Wu; Yuqi Guo; Hua Hu; et al. (Archives of Microbiology, 2024)

Remediation of As-contaminated soil by utilizing steel slag-based passivators with different Fe/Ca ratios: As bioavailability and passivation characterization - Yuliang Zhang; Zongwu Hou; Pingfeng Fu; Xiaofei Wang; Tianli Xue; Yuqi Chen (Journal of Cleaner Production, 2023)

Simultaneous stabilization of arsenic and antimony co-contaminated mining soil by Fe(Ⅱ) activated-Fenton sludge: Behavior and mechanisms - Yuliang Zhang; Zongwu Hou; Pingfeng Fu; Xiaofei Wang; Tianli Xue; Yuqi Chen (Environmental Pollution, 2023)

Passivation efficiency and mechanism of arsenic-contaminated mining soil with iron-based solid wastes in collaboration with ferrous sulfate - Yuliang Zhang; Zongwu Hou; Pingfeng Fu; Xiaofei Wang; Tianli Xue; Yuqi Chen (Journal of Environmental Chemical Engineering, 2023)

Multiple Dimensions of using Mesenchymal Stem Cells for Treating Liver Diseases: From Bench to Beside - Lijun Chen; Ning Zhang; Yuqi Huang; Qi Zhang; Yangxin Fang; Jiamin Fu; Yin Yuan; Lu Chen; Xin Chen; Zhenyu Xu; Yifei Li; Hiromi Izawa; et al. (Stem Cell Reviews and Reports, 2023)

A model for predicting the grain size distribution of an armor layer under clear water scouring - Hongsheng Fu; Yuqi Shan; Chao Liu (Journal of Hydrology, 2023)

Inhalation exposure assessment techniques on ventilation dilution of infectious respiratory particles in a retrofitted hospital lung function room - Yuqi Fu; Shuo Liu; Weiqi Guo; Qionglan He; Weijie Chen; Guohui Ruan; Hua Qian; Yi Wang; Li Liu (Building and Environment, 2023)

Strong photo-thermal coupling effect boosts CO2 reduction into CH4 in a concentrated solar reactor - Lei Xu; Yuqi Ren; Yiwei Fu; Maochang Liu; Fengfan Zhu; Miao Cheng; Jiancheng Zhou; Wenshuai Chen; Ke Wang; Nan Wang; Naixu Li (Chemical Engineering Journal, 2023)

Deep kimberlite prospecting and thrust-nappe structure: Analysis of diamond metallogenic belt in Wafangdian, China - Mishan Zhong; Guoren Zhang; Haitao Fu; Haipeng Wang; Zhenghong Liu; Jin Liu; ZiJie Wu; Fuliang Gao; Yongzhao Gao; Yuqi Pan; Fanglai Wan; Lei Yang; et al. (International Geology Review, 2023)

SLIT3 knockdown inhibited TGF-β-induced hepatic stellate cells activation by down-regulating YAP signal - Xiling Fu; Jiabao Chang; Damin Jiao; Mengying Zhu; Yuqi Ma (Molecular & Cellular Toxicology, 2023)
Objective Liver fibrosis is a chronic liver disease caused by a variety of pathophysiological. However, there are no effective treatments to combat it. HSCs are a major source of fibrotic cells and exploring the mechanisms of HSC activation may provide new strategies for the treatment of liver fibrosis. Objectives To explore the role and underlying mechanism of SLIT3 in HSCs fibrosis. Results GSE163211 dataset analysis identified aberrant expression of SLIT3 in NASH F1-F4 tissues and SLIT3 expression level was positively correlated with fibrosis-related proteins. In vitro experiments showed that TGF-β induced upregulation of SLIT3 in LX-2 cells. Knockdown of SLIT3 significantly inhibited TGF-β-induced α-SMA, COL1A2, and COL1A1 expression, inhibited excessive cell proliferation and migration, and suppressed YAP activity. Conclusion Collectively, our findings suggest that SLIT3 deficiency alleviates TGF-β-induced HSCs activation by inhibiting YAP activity.

How geographic diversification affects corporate social responsibility? The moderating effects of ownership and environmental regulation - Yi Zhang; Xinyuan Peng; Yuqi Li; Shuke Fu (Environmental Science and Pollution Research, 2022)

Using a global reference sample set and a cropland map for area estimation in China - Le Yu; XueCao Li; CongCong Li; YuanYuan Zhao; ZhenGuo Niu; HuaBing Huang; Jie Wang; YuQi Cheng; Hui Lu; YaLi Si; ChaoQing Yu; HaoHuan Fu; et al. (Science China Earth Sciences, 2017)

The relationship between human cytomegalovirus infection and atherosclerosis development - Ruizhen Chen; Sidong Xiong; Yingzhen Yang; Weiguo Fu; Yuqi Wang; Junbo Ge (Molecular and Cellular Biochemistry, 2003)